A framework of indirect taxation system in public finance from Syariah perspectives - Mohammad Sharif, Mohammad Radzi; Maamor, Selamah; Abu Bakar, Abu Sufian (2019)
The subject matter of public finance follows the development in state activities and corresponding economic philosophy. With the passage of time and policies of state, the scope of public finance expanded to cover more areas. The development of new political, economic, social, formulation of fiscal and monetary policies made profound differences in the present as compared to the past public finance problems. The fiscal system practiced by Muslim state in the past was consistent, operational, efficient and worked within the value of an Islamic society perspectives. The scholars of the period expressed practical wisdom and economic insight to bear on fiscal issues as evidenced by contribution of among others by Abu Yusuf Yaqub bin Ibrahim (d. 798 A.D.) which showed enormous economic insights in solving these problems and highlighted the distinctive value-based orientation of the mobilization of the resources of revenue and its disbursement in accordance with the objectives of Islamic Syariah. This article explores the model and wisdom of indirect tax practices as being implemented by past Islamic leaders in fulfilling their obligations towards managing the nation while protecting the people’s wellbeing.